Bilirubin Targeting WNK1 to Alleviate NLRP3‐Mediated Neuroinflammation - Linfei Mao; Jiayu Lu; Quanjun Yang; Zhenqi Liu; Cuiping Wu; Bingbing Ke; Kaiyan Su; Haolin Yuan; Yaqi Cui; Yao Wang; Richard Salvi; Guang Yang; et al. (Advanced Science)
Abstract Bilirubin, an endogenous metabolite with many significant physiological roles, particularly anti‐inflammatory properties, shows great promise as a treatment for inflammatory diseases. However, the binding targets and downstream signaling mechanisms of bilirubin remain unclear. Here, by using quantitative phosphorylation proteomics and several powerful chemical biology techniques such as the Cellular Thermal Shift Assay (CETSA), molecular docking, and MicroScale Thermophoresis (MST), it is identified and confirmed that with‐no‐lysine (K) kinase 1 (WNK1) is the primary target of bilirubin at physiological concentrations. Bilirubin binds to the kinase domain of WNK1, activating its kinase activity and increasing the intracellular chloride ion concentration via the downstream SPAK/OSR1‐KCC2 pathway in neurons. Manipulating endogenous bilirubin levels by deleting Blvra, the bilirubin synthesis enzyme, and Ugt1a1, its metabolic enzyme, significantly promotes and inhibits the activation of the lipopolysaccharide (LPS)‐induced NLRP3 inflammasome, respectively, in mouse hippocampus. Similarly, exogenous bilirubin supplementation suppressed LPS‐induced NLRP3 inflammasome activation in mouse hippocampus in a WNK1‐dependent manner. Quantitative phosphoproteomic analysis of WNK1 downstream signaling elucidated the broad biological roles of WNK1, notably its function in suppressing inflammation. The findings clarify the direct targets and signaling mechanisms underlying the anti‐inflammatory effects of bilirubin and pave the way for exploring its novel functions.